High systemic inflammation response index (SIRI) level as a prognostic factor for colorectal cancer patients after curative surgery: a single-center retrospective analysis - Tamuro Hayama; Hiroki Ochiai; Tsuyoshi Ozawa; Toshiya Miyata; Kentaro Asako; Yoshihisa Fukushima; Kensuke Kaneko; Keijiro Nozawa; Shoichi Fujii; Takeyuki Misawa; Takeo Fukagawa (Scientific Reports)
Abstract The Systemic Inflammation Response Index (SIRI), a marker used to assess systemic inflammation, is associated with lower patient survival rates in various cancer types. Factors contributing to the recurrence of colorectal cancer (CRC) have been examined previously using the preoperative SIRI. Herein, we investigated the association between the preoperative SIRI level and both the recurrence-free survival (RFS) and overall survival (OS) in patients diagnosed with CRC. We retrospectively analyzed the case of 406 patients who underwent curative surgery for Stage I-III CRC at a single institution during 2012- 2017. Based on their SIRI levels, we categorized the patients into a low-SIRI group (≤ 1700) and a high-SIRI group (> 1700). Multivariable analyses revealed that a high-SIRI level was an independent risk factor for 5-year RFS (p = 0.045) and OS (p = 0.048) in CRC patients. A Kaplan–Meier analysis demonstrated significantly poorer 5-year RFS and OS outcomes in the high-SIRI group compared to the low-SIRI group (p = 0.0001, p = 0.017 respectively). These findings suggest that the high-SIRI level is significantly associated with a poorer prognosis in patients diagnosed with CRC.